Internal Control and Budget Execution in Peruvian Municipalities - Alvarado Leguia, Angela Andrea (2024)
The study examined the relationship between internal control and budget execution in Peruvian municipalities. A representative sample of 53 municipal workers from two Peruvian provinces was selected based on basic research and a quantitative correlational methodology. In contrast, standardized surveys and questionnaires were employed as data collection instruments. These were evaluated for content and construct validity, as well as reliability, through the use of Cronbach's alpha to ascertain the internal consistency of the questionnaires. The results demonstrate that all the variables under investigation, including internal control, control environment, risk assessment, control activities, information and communication, and supervision, are significantly correlated with budget execution. These notable correlations indicate that enhancements in these domains could have a favorable influence on budget execution.